2020
DOI: 10.3892/mco.2020.2010
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheterization in cancer patients with severe thrombocytopenia: Ultrasound‑guide improves safety avoiding prophylactic platelet transfusion

Abstract: Prior research has revealed that ultrasound (US) guided central venous catheterization (CVC) is associated with a reduction in the complication rate such as pneumothorax and an improved first-pass success placing CVC in the internal jugular vein. The present study investigated if US-guided CVC, in a subset of cancer patients with severe thrombocytopenia, reduced bleeding risk and avoided prophylactic platelet transfusion. The efficacy and safety of US-guided CVC placement in cancer patients with severe thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
7
0
1
Order By: Relevance
“…DTTP, differential time to positivity; CVC, central venous catheter using a large sterile drape and implementing aseptic bundles as they decrease the risk of CRI [102,118]. Ultrasound (US)-guided central venous catheterization is associated with lower rates of pneumothorax and other mechanical complications and may reduce the number of cannulation attempts [119][120][121]. Although the impact on the incidence of CRI is less clear, central venous cannulation using US is recommended for the avoidance of mechanical complications and the reduction of cannulation attempts with a possible positive impact on the incidence of CRI [119,122].…”
Section: Education Bundles and Surveillancementioning
confidence: 99%
“…DTTP, differential time to positivity; CVC, central venous catheter using a large sterile drape and implementing aseptic bundles as they decrease the risk of CRI [102,118]. Ultrasound (US)-guided central venous catheterization is associated with lower rates of pneumothorax and other mechanical complications and may reduce the number of cannulation attempts [119][120][121]. Although the impact on the incidence of CRI is less clear, central venous cannulation using US is recommended for the avoidance of mechanical complications and the reduction of cannulation attempts with a possible positive impact on the incidence of CRI [119,122].…”
Section: Education Bundles and Surveillancementioning
confidence: 99%
“…The main advantage of ultrasound is the cost-effectiveness compared to MRI and flexibility of setting in which it can be used, moreover, it is demonstrated that ultrasound allows a higher spatial resolution than MRI thanks to modern high-frequency transducers (10–15 Mhz) [ 19 ], and the main disadvantage is represented by the accuracy that is operator-dependent. Another point not to forget is that ultrasound is used also to assess ultrasound-guide treatments, whose use has been widely adopted in many fields of medicine, such as catheterization in cancer patients [ 20 ], stem cell transplantation [ 21 ] and local anaesthetic infiltration [ 22 ]. Ultrasound became popular for its advantages, such as being minimally invasive, fast, easy to use and controlling the effectiveness of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Both variables have previously been described as risk factors for mechanical complications in general cohorts. 2,12,[14][15][16] Moreover, preprocedural coagulopathy was associated with grades 2-4 bleeding. In the majority of these bleedings, the patients were preprocedurally given platelets (Tables 4 and 5; Figure 2; File S1), yet coagulopathy was still correlated with moderate to severe bleeding.…”
Section: Ultrasound-guided Technique Was Used In the Majority Of Allmentioning
confidence: 99%